Passively Q-switched fiber laser utilizing new hafnium–bismuth–erbium co-doped fiber as saturable absorber - Rahman, Mohd Fauzi Ab; Latiff, Anas Abdul; Reddy, Pinninty Harshavardhan; Das, Shyamal; Dhar, Anirban; Paul, Mukul Chandra; Harun, Sulaiman Wadi (Springer Verlag (Germany), 2019)
A stable all-fiber passively Q-switched erbium-doped fiber laser emitting at 1559 nm is proposed and demonstrated using an 8-cm-long hafnium–bismuth–erbium co-doped fiber (HBEDF) as a saturable absorber (SA). The HBEDF is fabricated in-house and has a linear absorption of around 5.2 dB at the laser operating wavelength of 1559 nm. The Q-switching pulses are obtained with an input pump power ranging from 50 to 121 mW. It has the pulse repetition rate of 81.57 kHz, the shortest pulse width of 3.31 µs, output power of 10 mW, pulse energy of 123 nJ and peak power of 37.3 mW at the maximum pump power of 121 mW. The corresponding signal-to-noise ratio of the electrical spectrum is measured to be around 70 dB, which indicates the stability of the laser. To the best of our knowledge, this is the first demonstration of the deployment of HBEDF SA in generating a robust and steady pulsed laser in 1.5-micron region. © 2019, Indian Association for the Cultivation of Science.